Rapid Proton-Detected NMR Assignment for Proteins with Fast Magic Angle Spinning - Barbet-Massin, Emeline (American Chemical Society, 2014)
[Image: see text] Using a set of six (1)H-detected triple-resonance NMR experiments, we establish a method for sequence-specific backbone resonance assignment of magic angle spinning (MAS) nuclear magnetic resonance (NMR) spectra of 5–30 kDa proteins. The approach relies on perdeuteration, amide (2)H/(1)H exchange, high magnetic fields, and high-spinning frequencies (ω(r)/2π ≥ 60 kHz) and yields high-quality NMR data, enabling the use of automated analysis. The method is validated with five examples of proteins in different condensed states, including two microcrystalline proteins, a sedimented virus capsid, and two membrane-embedded systems. In comparison to contemporary (13)C/(15)N-based methods, this approach facilitates and accelerates the MAS NMR assignment process, shortening the spectral acquisition times and enabling the use of unsupervised state-of-the-art computational data analysis protocols originally developed for solution NMR.